2022
DOI: 10.1155/2022/5453420
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Metastatic Glioblastoma Diagnosed by Endobronchial Ultrasound-Transbronchial Needle Aspiration

Abstract: Glioblastoma is a common primary brain tumor that has a high mortality rate. Reports of intrathoracic metastases are uncommon, with the most commonly reported site for metastases are the lung and pleura. However, involvement of the mediastinum is not well documented, and few reports of confirmed mediastinal metastases diagnosed by endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) exist. Herein, we report a rare case of metastatic glioblastoma to the thorax. A lady in her 40s has been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As seen by the influx of published articles on the topic, these conditions are either a new aspect of glioma pathology or are just starting to be reconsidered and not misinterpreted [17][18][19]. Cervical masses, however, seem to be quite a common occurrence in the context of metastatic disease, as seen by the case reports published by Sun et al, Waite et al, Taha et al, and Baskurt et al, with almost all of the reported patients being males in their forties [5][6]17].…”
Section: Discussionmentioning
confidence: 99%
“…As seen by the influx of published articles on the topic, these conditions are either a new aspect of glioma pathology or are just starting to be reconsidered and not misinterpreted [17][18][19]. Cervical masses, however, seem to be quite a common occurrence in the context of metastatic disease, as seen by the case reports published by Sun et al, Waite et al, Taha et al, and Baskurt et al, with almost all of the reported patients being males in their forties [5][6]17].…”
Section: Discussionmentioning
confidence: 99%